CHAMPION SPIRITUALITY – AS THE BASIS OF VICTORY - Rashidov Zuxriddin Najim o'g'li (Journals Park Publishing, 2024)
Everything begins with a relentless pursuit of perfection and a solid confidence in its ability. Winning athletes have mental stiffness, which allows them to maintain peace of mind under pressure and get back from setbacks and be stronger than ever before. They come to the sport with the idea of constant growth, seeing every challenge as an opportunity to learn and expand their reach.
Keywords: victory, athlete, human thinking, discussion, thought.